Association of Coagulation Factors with Pathogenesis of Canine Parvovirus; an Insight into Disease Pathogenesis & Its Diagnosis (Journal of Agriculture and Veterinary Science, 2025)
Canine Parvovirus (CPV) is a virus of the genus Protoparvovirus (family Parvoviridae, subfamily Parvovirinae). CPV is a single-stranded, small, non-enveloped DNA virus. Canine parvovirus is a virus that can cause acute hemorrhagic enteritis and, infrequently, fatal myocarditis in dogs. Non-immunized puppies are particularly susceptible, and the virus causes severe enteritis along with anorexia, depression, increase temperature, vomiting, rapid dehydration, and bloody diarrhea. The present study was conducted to investigate that during the pathogenesis of parvovirus, three coagulation factors (Factor IIa, IXa, and Xa) were affected due to decrease in Antithrombin III activity. The blood samples of 50 dogs of different ages, infected with canine parvovirus were collected from different clinics and from Pet center UVAS, Lahore. Then by using automation method we had run these samples in the coagulation analyzer CS-1600, it worked on multiwavelength detection or photo optical clot detection principle. The CS-1600 has an optical cable that can supply light of various wavelengths and a sensor that can receive light of various wavelengths. A variation in optical density (OD) of a test sample is used to identify clot formation in the photo optical method. Results of coagulation factors were in the form of percentages and clotting time in seconds. all these three coagulation factors were elevated from their normal reference range. Hypercoagulation was further confirmed by the increased prothrombin time, activated partial thromboplastin time.